Interleukin 21 receptor/ligand interaction is linked to disease progression in pancreatic cancer - Linnebacher, Alica; Mayer, Philipp; Marnet, Nicole; Bergmann, Frank; Herpel, Esther; Revia, Steffie; Yin, Libo; Liu, Li; Hackert, Thilo; Giese, Thomas; Herr, Ingrid; Gaida, Matthias (Cells, 2019)
Pancreatic ductal adenocarcinoma (PDAC) displays a marked fibro-inflammatory microenvironment in which infiltrated immune cells fail to eliminate the tumor cells and often—rather paradoxically—promote tumor progression. Of special interest are tumor-promoting T cells that assume a Th17-like phenotype because their presence in PDAC tissue is associated with a poor prognosis. In that context, the role of IL-21, a major cytokine released by Th17-like cells, was assessed. In all tissue samples (n = 264) IL-21+ immune cells were detected by immunohistochemistry and high density of those cells was associated with poor prognosis. In the majority of patients (221/264), tumor cells expressed the receptor for IL-21 (IL-21R) and also a downstream target of IL-21, Blimp-1 (199/264). Blimp-1 expression closely correlated with IL-21R expression and multivariate analysis revealed that expression of both IL-21R and Blimp-1 was associated with shorter survival time of the patients. In vitro data using pancreatic tumor cells lines provided a possible explanation: IL-21 activated ERK and STAT3 pathways and upregulated Blimp-1. Moreover, IL-21 increased invasion of tumor cell lines in a Blimp-1-dependent manner. As an in vivo correlate, an avian xenograft model was used. Here again Blimp-1 expression was significantly upregulated in IL-21 stimulated tumor cells. In summary, our data showed an association of IL-21+ immune cell infiltration and IL-21 receptor expression in PDAC with poor survival, most likely due to an IL-21-mediated promotion of tumor cell invasion and enhanced colony formation, supporting the notion of the tumor-promoting abilities of the tumor microenvironment.
Gesehen am 31.10.2019